Corporate entrepreneurship as an answer to an ever-changing economy - Soltanifar, Mariusz (Henry Stewart Talks, 2020)
Innovation, Entrepreneurship, 3M’s corporate entrepreneurship, Supply chain transformation, Overcoming challenges in a corporation